RELATIONSHIP OF JOINT HYPERMOBILITY AND MUSCULOSKELETAL PROBLEMS AND FREQUENCY OF BENIGN JOINT HYPERMOBILITY SYNDROME IN CHILDREN - Qureshi, Ahmad Usaid; Maalik, Abdul; Ahmad, Tahir Masood (Journal of Ayub Medical College Abbottabad, 2010)
Background: The majority of individuals with joint hypermobility remain asymptomatic. However, those associated with Benign Joint Hypermobility Syndrome (BJHS), develop a number of systemic manifestations. Our objective was to determine the relationship between joint hypermobility and musculoskeletal problems, and frequency of BJHS in children and adolescents. Method: This crosssectional observational descriptive study was conducted at Outpatient Department, The Children's Hospital, Lahore, Pakistan. A total of 872 individuals (4-18 year) were examined for hypermobile joints using Beighton score ‰¥4. A questionnaire was implied to get data regarding demographic profile, musculoskeletal and extra-articular complaints, family history of joint problems and daily activity. Brighton's criteria were implied for diagnosis of BJHS. Results: The frequency of joint hypermobility was 37.0%; male 39.5%, and female 34.2% (p=0.1). There was a gradual decline in mean Beighton score with age. The female population showed increase in mean Beighton score around 16-17 year age. Arthralgias and back pains 7.7% vs. 1.6%, (p<0.001), and hernias 2.5% (p=0.03) were significantly higher in individuals with joint hypermobility. History of joint problems in the family was also significantly higher in children with joint hypermobility (p=0.01). BJHS was detected in 4.8% children (male 3.6% and female 6.3%, p=0.06). Arthralgias (51.0%), hernias (16.3%), joint dislocations (8.2%) and varicose veins (8.2%) were the most common presentations. Conclusion: BJHS is common among children. Arthralgias, back pains and hernias are significantly higher in these individuals. Keywords: Joint hypermobility, Benign Joint Hypermobility Syndrome, musculoskeletal problems, Children